ChemInform Abstract: One‐Step Synthesis of Diazaspiro[4.5]decane Scaffolds with Exocyclic Double Bonds. Issue 1 (January 2015) - Li, Lidong; Hu, Qiong; Zhou, Pingping; Xie, Haifeng; Zhang, Xiaorong; Zhang, Hao; Hu, Yadong; Yin, Fei; Hu, Yimin
Abstract 27 examples